2006
DOI: 10.1097/01.olq.0000200609.77577.3f
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Costs, Effectiveness, and Disease Control of a Population-Based Program Using Home Sampling for Diagnosis of Urogenital Chlamydia trachomatis Infections

Abstract: Home sampling should be considered a relevant alternative to the current practice of in-office screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 42 publications
0
39
2
1
Order By: Relevance
“…For example, as in the studies by Roberts et al 25 and Adams et al ,3 we adopted a probability of 10% for the progression from undiagnosed female chlamydia infection to pelvic inflammatory disease. This is in contrast to the studies by Andersen et al ,21 Gift et al ,22 Welte et al 23 and deVries et al ,24 which adopted equivalent probabilities of 25%, 20%, 20% and 15%, respectively. In all studies, this parameter has been shown to be a major influence on cost-effectiveness, and recent evidence appears to support the more conservative approach used here in the modelling of this relationship 26.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…For example, as in the studies by Roberts et al 25 and Adams et al ,3 we adopted a probability of 10% for the progression from undiagnosed female chlamydia infection to pelvic inflammatory disease. This is in contrast to the studies by Andersen et al ,21 Gift et al ,22 Welte et al 23 and deVries et al ,24 which adopted equivalent probabilities of 25%, 20%, 20% and 15%, respectively. In all studies, this parameter has been shown to be a major influence on cost-effectiveness, and recent evidence appears to support the more conservative approach used here in the modelling of this relationship 26.…”
Section: Discussionmentioning
confidence: 60%
“…Our cost-effectiveness results can also be compared to those from other studies, which, using alternative dynamic modelling frameworks, reported conflicting results for the cost-effectiveness of chlamydia screening strategies in various countries. Andersen et al ,21 Gift et al ,22 Welte et al 23 and deVries et al 24 individually found that various forms of opportunistic and proactive screening were cost effective in Denmark, the USA and the Netherlands. Conversely, Roberts et al 25 found that proactive register-based screening in the UK was not cost effective.…”
Section: Discussionmentioning
confidence: 99%
“…All future disease states were counted in the year of asymptomatic infection, applying discounting to correct for the age-specific expected delay between infection and its consequences for pregnancy, infertility and offspring. The model was an updated version of a previously developed model,8 9 15 with two additions: (1) the option to perform probabilistic sensitivity analysis and (2) the inclusion of direct effects for treated persons. In order to define the total costs of Chlamydial infections detected in different scenarios, we multiplied the number of infections and sequelae by their estimated costs.…”
Section: Methodsmentioning
confidence: 99%
“…The costs of screening were estimated based on the actual programme budgets of STI AIDS Netherlands, the central coordinating organisation for the CSI project, and the three regional Public Health Services involved in CSI. Costs for the treatment of Chlamydia and its sequelae, as well as costs associated with productivity losses, were updated and adapted from previous models8 9 15 or taken from recent literature. To calculate outcomes in terms of QALYs, we used data on the duration of MO and quality of life losses associated with MO, as provided by Stratton et al 16.…”
Section: Methodsmentioning
confidence: 99%
“…Dynamische modellen lijken hier een uitweg te bieden en geven over het algemeen sneller kostenbesparingen. [24][25][26] Bovendien worden aanzienlijke prijsreducties in testprijzen verwacht bij grootschaliger gebruik en kunnen laboratoriumtechnieken zoals 'poolen' van testmonsters de testkosten van een screeningsprogramma met de helft reduceren. 27 10.…”
Section: Er Moet Consensus Bestaan Over Wie Men Als Patiënt Beschouwtunclassified